Development of cognitive interest in the study of mathematics among students majoring - Muhamedzhanovna Mustafina,, Nella Fuatovna Abayeva, Lezzetzhan; Ivanovna Yerakhtina, Irina; Bayan Shingisovna Alimova, Vitaliy Vladimirovich Zhurov, (Opción, 2019)
The purpose of the research is to theoretically substantiate and practically develop the system of fostering cognitive interest in the study of mathematics among students majoring in mining via comparative quantitative research methods. The results of the teaching experiment show that the students in the experimental group have a higher quality of mathematical competency. In conclusion, to test the hypothesis that introduction of the instructional system in the learning process in college would enhance the level of mathematical competency of students, the final academic achievement of the students involved in the experiment was assessed for mathematical disciplines